Transforming The Institutional and Governance Frameworks of Indonesia’s Downstreaming Policy - Bahlil Lahadalia; Chandra Wijaya; Athor Subroto (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Despite the significant benefits generated by Indonesia's downstreaming strategy, including a substantial increase in exports and investments, there remains considerable potential for further refinement. The implementation of this policy is hindered by ineffective coordination among various ministries and stakeholders. Purpose: This paper seeks to address the existing governance and institutional challenges that obstruct effective policy execution through an integrative literature review and comparative analysis. Finding/Result: Drawing insights from the successful industrial policies of China, South Korea, and the United States, this research found the existing discrepancy in the institutional and governance arrangements between Indonesia’s downstreaming policy and the best practice from other countries which accentuate the necessity for vigorous reforms.Conclusion: This research offers novel insights into the discourse on downstreaming policy by examining its institutional design and governance frameworks.Originality: The paper provides practical recommendations aimed at enhancing the institutional design and governance of downstreaming, thereby aligning the policy more closely with its stated objectives. Keywords: institutional policy, downstreaming industry, industrial policy, governance, coordination agency